Independence day. Resurgence [videorecording (DVD)] - Emmerich, Roland (Twentieth Century Fox Home Entertainment LLC, 2016)
Using recovered alien technology, the nations of Earth have collaborated on an immense defense program to protect the planet. But nothing can prepare people for the aliens' advanced and unprecedented force. Only the ingenuity of a few brave men and women can bring the world back from the brink of extinction.